Toxoplasma gondii : isolamento, caracterização biológica e molecular de amostras provenientes de galinhas (Gallus gallus domesticus) em propriedades rurais do Estado do Espírito Santo, Brasil - Ferreira, Tamiris Cristine Ribeiro (2016)
Toxoplasma gondii, source of toxoplasmosis, is able to infect a wide variety of animals and presents high prevalence worldwide. Felines are considered the parasite’s definitive hosts. Among the intermediate hosts, mammals (including the man) and birds are the most important. Humans can be infected by the ingestion of tissue cysts present in the meat of processed birds. In this manner, it is important to know the parasite’s biological and molecular aspects, enabling higher integration to its epidemiology. In this study, taken place in the state of Espírito Santo, Brazil, 57 free-range chickens used for human consumption were submitted to serological trial using indirect hemagglutination. From these, 13 chickens were considered positive. The hearts and brains of five positive chickens were collected, pepsinized and inoculated separately in two female Swiss mice via intraperitoneal injection. Tachyzoites were observed in the peritoneum of all these animals between seven and ten days after inoculation.10 isolates were obtained and maintained by successive culture with brain cists. To biologically characterize the isolates, groups of 5 female BALB/C mice were inoculated with 101 , 102 , 103 , 104 tachyzoites per animal. All isolates were considered virulent or with intermediate virulence, that is, no infected animal has survived after a 30-day observation period. The molecular characterization of the isolated, performed by PCR-RFLP, has demonstrated the occurrence of three distinct genotypes. No isolated has presented clonal genotypes (types I, II or III) or Brazil’s clonal lineage (BrI, BrII, BrIII and BrIV). There was no molecular differences (PCR-RFLP patterns) observed between the isolates obtained from the brain or heart of the same bird. Two isolates had already been reported in literature as source of diseases in humans. These results contributed to identify the circulating strains in the Espírito Santo region that have already been identified in other places in Brazil and around the globe.